Effect of hydrocarbons on the ammonia selective catalytic reduction of nitrogen oxides under typical diesel engine exhausts conditions over copper-based zeolites (2020)
ABSTRACT: The use of diesel engines is growing due to their advantages over the gasoline engines, but they increase nitrogen oxides (NOX) emissions. The ammonia selective catalytic reduction (NH3-SCR) with Cu-based zeolites is the most promising and studied technique for the abatement of NOX. However, research under more realistic conditions, such as including hydrocarbons on the simulated gas, needs to be studied deeply. We selected Cu-ZSM-5, Cu-SSZ-13, and Cu-SAPO-34 (three of the most successful and investigated catalysts in the NH3-SCR of NOX) to perform a series of experiments regarding the effect of propylene and dodecane (two hydrocarbons that can be present in diesel exhausts) on the NH3-SCR of NO and adsorption of NH3. We synthesized the catalysts by ion exchange and confirmed their structure by X-ray diffraction. We found that both propylene and dodecane reduced the amount NH3 adsorbed on the catalysts. Also, we determined that experiments of temperature-programmed desorption of NH3 of Cu-ZSM-5 and Cu-SAPO-34 saturated with propylene changed the parameters of the desorption kinetic of the catalysts, and mainly affected the acid sites that not concern copper. We confirmed that dodecane (a long-chain hydrocarbon) affected the performance of Cu-SSZ-13 (a small-pore zeolite) on the NH3-SCR and NH3oxidation. Finally, we found that the hydrocarbons decreased the activation energy and changed the parameters of a power-law kinetic of Cu-ZSM-5 and Cu-SSZ-13 in the NH3-SCR of NO.